2022
DOI: 10.1007/s43076-022-00196-1
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Experiences and Coping During the COVID-19 Lockdown and Unlock in India

Abstract: In response to the coronavirus pandemic, the Government of India imposed a nationwide lockdown of 21 days on May 25, 2020, which was extended thrice to a total of 68 days. Mandatory quarantine could hamper mental well-being, trust in the government, and compliance with guidelines. This study looks in-depth at individual accounts during the lockdown (phase A) and after the “unlock” (lifting of the nationwide lockdown; phase B) using telephonic interviews. Mass job loss and the exodus of migrant workers from maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Other studies conducted in Columbia and Saudi Arabia also showed a higher prevalence of self-treatment, 60 , 61 pointing to the necessity for addressing the factors that drive individuals to self-medicate of which the most common were fears related to infection, quarantine, and societal stigma were the predominant motivations for self-medication. 62 , 63 However, studies done on self-medication during COVID-19 pandemic in: United States 13%, Australia 11%, Germany 11%, Spain 9%, United Kingdom 9%, Mexico 8%, and Italy 8% 64 showed disparity with the current report which may be due to drug policies and better health infrastructure. Nonetheless, this reflects the heightened anxiety and concerns prevalent during the pandemic, emphasizing the need for clear communication and support mechanisms.…”
Section: Discussionmentioning
confidence: 66%
“…Other studies conducted in Columbia and Saudi Arabia also showed a higher prevalence of self-treatment, 60 , 61 pointing to the necessity for addressing the factors that drive individuals to self-medicate of which the most common were fears related to infection, quarantine, and societal stigma were the predominant motivations for self-medication. 62 , 63 However, studies done on self-medication during COVID-19 pandemic in: United States 13%, Australia 11%, Germany 11%, Spain 9%, United Kingdom 9%, Mexico 8%, and Italy 8% 64 showed disparity with the current report which may be due to drug policies and better health infrastructure. Nonetheless, this reflects the heightened anxiety and concerns prevalent during the pandemic, emphasizing the need for clear communication and support mechanisms.…”
Section: Discussionmentioning
confidence: 66%
“…The goal is to identify the social and psychological processes that have contributed to making these young people vulnerable. As observed, the COVID-19 crisis exposed most people in precarious situations to vulnerability (Meraj & Makkar, 2022;Panteli et al, 2022;Stanistreet et al, 2020). One research question is to identify the characteristics of the COVID-19 pandemic as a career shock (Akkermans et al, 2018) and to identify to what extent it has mobilized personal resources, particularly psychological capital (Luthans et al, 2007;Urbanaviciute et al, 2019), as well as coping strategies (Breakwell, 1986).…”
Section: The Sustainability Model To Support Vulnerable Young People ...mentioning
confidence: 99%
“…The pandemic constituted a “career shock” for many of them, an experience defined as “a disruptive and extraordinary event that is at least to some degree caused by factors outside the focal individual's control and that triggers a deliberate thought process concerning one's career” (Akkermans et al, 2018, p. 4). This shock was particularly severe among disadvantaged young people (Blustein et al, 2022; Meraj & Makkar, 2022; Panteli et al, 2022). The short-term impact of the pandemic on employment, living conditions, education (Stanistreet et al, 2020), and health (Khlat et al, 2022) has been clearly identified.…”
Section: Introductionmentioning
confidence: 99%